Report on Endo- and Ecto-Parasites in Asian Elephants from Tamil Nadu, India - Elangovan, Tamileniyan; Murugesan, Jeevitha; Vasanthi Murugan, Thayanithi; Krishnamurthy, Rajeshkumar; Annamalai, Latchumikanthan; Muthusamy, Veeraselvam; Rangasamy, Velusamy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The occurrence of endo-and ecto-parasites were studied in semi-intensive reared elephants (n=26) of Theppakadu elephant camp,  Mudhumalai Tiger Reserve, Tamil Nadu. Dung samples and ectoparasites were collected from the maintained elephants. Evidence of ova  of Strongyle, Strongyloides sp., Bivitello bilharzianairi and mixed helminthic infections were observed. Lice collected from the ear, groin  and tail regions were identified as Haematomyzus elephantis. Larvae of Cobboldia elephantis was also detected in the faecal samples.  The present study emphasizes the occurrence of various endo- and ecto-parasitic infections in Asian elephants from Tamil Nadu, India
Keywords: Asian elephants; Cobboldia; Haematomyzus; Helminths; Tamil Nadu